Approximate gestures : infinite spaces in the fiction of Percival Everett - Stewart, Anthony, 1964- (Louisiana State University Press, 2020)
"In "Approximate Gestures," Anthony Stewart argues that the writing of Percival Everett, the acclaimed author of Erasure and more than twenty other works of fiction, compels readers to retrain their thinking habits and to value uncertainty. Stewart maintains that Everett's fiction challenges its interpreters to question their assumptions, consider the spaces in between categories, and embrace the potential of a larger, more uncertain world in an effort to confront bigotry and similarly limiting patterns of thought. Drawing on the work of Gilles Deleuze and Félix Guattari, Stewart proposes that their notion of the schizorevolutionary figure captures the in-between status of many of Everett's characters as they refuse the constraints of the binary, categorical structures that govern so much of human life. "Approximate Gestures" engages specifically with the vexed question of discussing race in Everett's fiction. Stewart frames the stakes of analyzing such subject matter in the writing of an African American novelist whose work rigorously questions critical approaches to race. Requiring readers to engage with black males who are hydrologists, ranchers, college professors, romance novelists, and in one case, a toddler, means entering a world released from habitual frames of reference. Through an examination of a broad selection of novels, Stewart demonstrates the extent to which Everett's characters inhabit "infinite spaces in between conventional categories" and understand themselves as subjects attempting to navigate social and psychological worlds. "Approximate Gestures: Infinite Spaces in the Fiction of Percival Everett" encourages readers and critics to think more deeply about how they position themselves in and engage with the world around them. As one of the first books of literary criticism devoted to Everett's fiction, Stewart's pathbreaking study models a method for reading the formidable body of work being produced by a major contemporary writer"--